Pengaruh Permainan Bolang Kecil Terhadap Keterampilan Sains Anak Usia Dini - Oney Novaria Safitri (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The background of this study is the lack of ability to understand science learning in early childhood at KB TK Islam Al-Fatah, driven by the absence of effective learning innovations implemented by teachers at school, resulting in the age of children who should have understood the concept of science being hampered. The Small Bolang game is an alternative for learning science that is adjusted to the abilities of early childhood while still paying attention to aspects of learning and playing that are fun. The purpose of this study is to determine the effect of the Small Bolang game on the science skills of early childhood. Data collection was carried out through observation activities. Analysis of research data used a quantitative approach using the experimental method. The research design used in this study was Quasi Experiment Design. The results of this study indicate that there is a significant influence of the Small Bolang game on the science skills of early childhood.